Ultrastructure and Dynamics of Synaptonemal Complex Components During Meiotic Pairing and Synapsis of Standard (A) and Accessory (B) Rye Chromosomes - Hesse, Susann; Zelkowski, Mateusz; Mikhailova, Elena I.; Keijzer, Christian J.; Houben, Andreas; Schubert, Veit (Frontiers in Plant Science, 2019)
During prophase I a meiosis-specific proteinaceous tripartite structure, the synaptonemal complex (SC), forms a scaffold to connect homologous chromosomes along their lengths. This process, called synapsis, is required in most organisms to promote recombination between homologues facilitating genetic variability and correct chromosome segregations during anaphase I. Recent studies in various organisms ranging from yeast to mammals identified several proteins involved in SC formation. However, the process of SC disassembly remains largely enigmatic. In this study we determined the structural changes during SC formation and disassembly in rye meiocytes containing accessory (B) chromosomes. The use of electron and super-resolution microscopy (3D-SIM) combined with immunohistochemistry and FISH allowed us to monitor the structural changes during prophase I. Visualization of the proteins ASY1, ZYP1, NSE4A and HEI10 revealed an extensive SC remodelling during prophase I. The ultrastructural investigations of the dynamics of these four proteins showed that the SC disassembly is accompanied by the retraction of the lateral and axial elements from the central region of the SC. In addition, SC fragmentation and the formation of ball-like SC structures occur at late diakinesis. Moreover, we show that the SC composition of rye B chromosomes does not differ from that of the standard (A) chromosome complement. Our ultrastructural investigations indicate that the dynamic behaviour of the studied proteins is involved in SC formation and synapsis. In addition, they fulfil also functions during desynapsis and chromosome condensation to realize proper recombination and homologue separation. We propose a model for the homologous chromosome behaviour during prophase I based on the observed dynamics of ASY1, ZYP1, NSE4A and HEI10.